METHODS OF TREATMENT AND/OR PREVENTION OF MAJOR ADVERSE CARDIOVASCULAR EVENTS (MACE) WITH A COMBINATION OF A BET BROMODOMAIN INHIBITOR AND A DIPEPTIDYL PEPTIDASE 4 INHIBITOR - KHAN, Aziz, Naeem; LEBIODA, Kenneth, Eugene; HALLIDAY, Christopher, Ross Armstrong (2024)
Described herein are methods of for treating and/or preventing Major adverse cardiovascular events (MACE) by administering to a subject in need thereof, a combination of a dipeptidyl peptidase 4 (DPP-4) inhibitor and a compound of Formula I or a stereoisomer, tautomer, pharmaceutically acceptable salt, or hydrate thereof, wherein the variables of Formula I are as defined herein.